Transfer of Training: Improving the Effectiveness of Employee Training in Nepal - Subedi, Bhawani Shankar (Journal of Education and Research, 2008)
This paper presents a summary, conclusions and recommendations of a recent doctoral study titled ‘Transfer of Training: Improving the Effectiveness of Employee Training in Nepal’. The purpose of this study was to examine the extent of transfer and to identify factors influencing it in the context of civil and corporate sector organizations of Nepal. This cross sectional descriptive research included stratified random samples of organizations from four development regions of Nepal. Data were collected from 299 cases (56 managers, 78 supervisors and 165 employees, who received training within the last twelve months) using a mail survey, on-site survey, personal interviews, focus group discussions, training evaluation models, and observations for the verification of workplace evidences of transfer or non-transfer of the training. DOI: http://dx.doi.org/10.3126/jer.v1i0.7951 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 51-61